Tissue-specific amino acid accumulation in Cynomorium songaricum stem and epidermis responds to distinct water and soil cues - Yu Tang; Xunchao Zhang; Yang Yang; Wenshu Wang; Jie Wang; Yubi Zhou (PLoS ONE, 2026)
This study provides the first evidence, from the perspective of intra-organ metabolic division of labour, that Cynomorium songaricum adapts to the heterogeneity of desert habitats through a synergistic strategy of “stem epidermis perceiving the water environment and fleshy stem buffering soil stress.” The research found a significant spatial metabolic division within the organs of C. songaricum : the stem epidermis is enriched in various essential and functional amino acids, including threonine and serine, with their content significantly higher than in the fleshy stem. In contrast, the fleshy stem specifically accumulates proline and cysteine, showing a significant difference. Environmental driving analysis indicates that, although C. songaricum is a holoparasitic root parasite, the metabolic division within its organs is still significantly driven by differential rhizosphere soil-water environmental factors: the amino acid profile of the stem epidermis is sensitive to water environmental factors such as electrical conductivity and carbonate ions, showing a positive correlation; whereas the amino acid composition of the fleshy stem is mainly regulated by soil factors such as water-soluble salts, showing a negative correlation. This suggests that, even while relying on the host for nutrition, the metabolic characteristics of C. songaricum are still influenced by its growth micro-environment. This finding breaks through the research paradigm of treating plants as homogeneous entities, providing new insights into understanding plant ecological adaptability and offering a key scientific basis for the artificial adaptive management and comprehensive utilization of C. songaricum resources.